Stars and Galaxies - Buckley, James, Jr.; Smith, Grace Hill; Romero, Libby; Weglinski, Michaela (London : Dorling Kindersley Limited, 2023)
Introduces stars and galaxies, describing how stars form constellations and the Earth's place in the galaxy, and provides tips for stargazing.
Includes index
Includes questions and exercises
Keywords: Astronomy -- Juvenile literature; Galaxies -- Juvenile literature; Readers (Primary) -- Juvenile literature